A critical review on heat transfer in trickle bed reactors - Taulamet, María José (2015)
A critical review of the available information about heat transfer between a packed bed with cocurrent downflow of gas and liquid and an external medium is undertaken. Several aspects as experimental set-ups and methods employed to study heat transfer in TBR, models used to interpret experimental data and literature correlations of heat transfer parameters are addressed. From the analysis of the available experimental information a refined database has been built, which allows comparing the performance of the existing correlations for the parameters of the extensively employed two dimensional pseudohomogeneous plug flow model (i.e., effective radial thermal conductivity and wall heat transfer coefficient). In addition, new correlations for the effective thermal conductivity have been developed. Identification of gaps in the current knowledge and recommendations for future works are summarize.